Defect engineering in SnO2 nanomaterials: Pathway to enhance the biohydrogen production from agricultural residue of corn stover. (December 2020) - Nadeem, Faiqa; Jiang, Danping; Tahir, Nadeem; Alam, Mujeeb; Zhang, Zhiping; Yi, Wang; Chaoyang, Lu; Zhang, Quanguo
Highlights: High quality NPs of SnO2 with size distribution of 5–10 nm were fabricated. Oxygen vacancies were controlled by annealing NPs in various environments. Maximum red shift in band energy of 0.56 eV was observed in reducing environment. 23.636% increase in THY was achieved with NPs annealed in reducing environment. ORP variation is correlated with OVs, higher number of OVs leads to lower ORP value. Abstract: It has been shown that altering nanomaterials through surface defects engineering (creation of oxygen vacancies) can be possible route to enhance the hydrogen production from agricultural residue of corn stover. Surface defects of oxygen vacancies in SnO2 nanoparticles were controlled through subsequent annealing in various environments such as oxygen (O), air and reducing gas (Ar95%+H2 5%). Scanning electron microscope (SEM) and x-ray diffraction (XRD) were performed to analyze the morphology and crystalline structure. Diffuse reflectance spectroscopy was employed to study the reflectance spectra. Annealing atmosphere showed profound effect on band energy where red shift in band energy of Δ = 0.28 eV and Δ = 0.56 eV were observed after annealing in air and reducing gas respectively. In relation to control group, nanoparticles annealed in reducing and air environment showed increase in hydrogen production rate and accumulated hydrogen production of 25.64% (147 mL/h), 23.636% (345 mL) and 16.24% (136 mL/h), 11.83% (312 mL) respectively. Reducing environment helped to generate more oxygen vacancies which enhances charge transfer mechanism, and eventually increases the metabolic rate to enhance the hydrogen production. Present work shows the novel pathway to regulate the charge flow to enhance the fermentative hydrogen production. Graphical abstract: Image, graphical abstract